PENGARUH PENGGUNAAN MINERAL LOKAL ZEOLIT ALAM TERHADAP KARAKTERISTIK SELF-COMPACTING CONCRETE (SCC) - Zacoeb, Achfas; Syamsudin, Ristinah; Poerwadi, Mahmud Rekarifin (Jurnal Mahasiswa Jurusan Teknik Sipil, 2014)
Self-Compacting Concrete (SCC) is a technological innovation in the manufacture of concrete that does not require compaction process to occupy formwork and solidified himself. In this research the manufacture of SCC used to harness the potential of local natural zeolite material. The research was conducted through the manufacture of test specimens in 3 variations SCC without natural zeolite and natural zeolite were added levels of 5%, 10%, and 15% of the weight of the cement used in the mix with the use slump flow additon of 1.5% of the weight of cement and FAS used at 0.49. Tests were performed is testing setting time, filling ability and strength of concrete. It also conducted a cost analysis comparison between SCC without natural zeolite with SCC using natural zeolite. Research results obtained are given natural zeolite levels affect the setting time of SCC, the higher levels of natural zeolite as a partial replacement of cement given the longer time required to reach the initial and final setting time. Filling ability of concrete increased accordingly increase the amount of natural zeolites are given optimum compressive strength obtained at 28 days was 28.06 MPa with high levels of natural zeolite were given by 10%. If viewed from the increased variety of natural zeolite with a compressive strength of concrete produced, the optimum value obtained from the regression equation y = -0,0605x2-1,3865 amounted to 11.45%. The use of natural zeolite as a partial replacement for cement can reduce the cost of making SCC. However, SCC manufacture using natural zeolite does not have significant difference when viewed from the economical. Keywords: Cost analysis,  compressive strength, natural zeolite, SCC, setting time,